Development of Indonesian Literature Textbook with Character Education Through Information and Communication Technology (ICT) Learning Based - Winarni, Retno; Y. Slamet, St.; Saddhono, Kundharu (International Journal of Engineering and Technology, 2018)
The objectives of this research were: (1) to describe the students’ and teachers’ needs on Indonesian literature textbook with characteristic education using ICT learning based, (2) to describe the development of Indonesian literature textbook model using ICT learning based, (3) to describe the effectiveness of the textbook using ICT learning based, 4) to describe the result of textbook dissemination using ICT learning based. The type of research used was research and development proposed by Borg and Gall. Research which was done through 4 stages, namely: (1) exploration, (2) model development, (3) model testing, and (4) dissemination. The exploratory stage used a qualitative descriptive approach. Data collection was done through document study, observation, interview, and questionnaire. Data analysis technique used was interactive analysis model. Model testing was done through experimental research. The results of this research were: (1) exploration stage showed that Indonesian literature textbook used in Public Elementary School 15, Public Elementary School 02 Kleco, and Public Elementary School 2 Sumber Surakarta had not been in accordance with the students’ and teachers’ needs, (2) Indonesian textbook was developed through preliminary field testing; and (3) model testing phase was done through experimental research in the main field testing. The value of tobtained (0.43) was then consulted to the value of ttable (with N = 90, α = 0.05) which was 1.64 so critical area {t <-1.64 or t> 1.64}. It could be concluded that tobtained (0.43) < ttable, as a result, H0 was accepted and the research was stated significant. In conclusion, Indonesian textbook with character education was effective to improve students' receptive skills.